A Robust Multilayer Dielectric Elastomer Actuator. Issue 1718 (2015) - Wolak, Mason A.; Zhu, Lei
ABSTRACT: We recently fabricated and characterized a new class of multilayer dielectric elastomer films comprising alternating layers of two different polymers, at least one of which is an elastomer. The films discussed here contain THV (a terpolymer of poly(vinylidene fluoride)) and poly(ethylene octene) [EO] elastomer. The multilayer structure provides improved dielectric and electromechanical performance relative to monolithic films of THV or EO. These properties are controlled by the composition and the layer structure. For example, increasing the concentration of the elastomeric EO component increases the maximum axial strain ( s z). Layering EO with THV also increases the breakdown strength ( E B ∼ 265 - 300 V/µm) relative to monolithic EO ( E B ∼ 150 V/µm) or THV ( E B ∼ 245 V/µm) control films. This enhancement in breakdown strength is consistent with a barrier effect that is also observed in multilayer polymer capacitor films. The increase in breakdown strength allows 512-layer 75 vol% EO / 25 vol% THV films to achieve maximum axial strains of s z nearly 4%, higher than can be attained by either EO or THV films alone. In addition, layering reduces remnant strain and electromechanical hysteresis by limiting the effective field within the THV layers. The 75% EO/ 25% THV films show robust operational longevity with little loss in axial strain when subjected to repeated actuation at E max = 225 V/µm (producing s z = 2.2%). Under these conditions, we observe 3, 000 consecutive actuation cycles with no electrical breakdown. In comparison, single component EO control films undergo electrical breakdown at this field and THV control films survive only a few hundred actuation cycles under these conditions. The results demonstrate that multilayering is an effective technique to increase the dielectric strength of elastomer materials and in turn improve upon strain and operational longevity (repeated actuation cycles) characteristics.